PENGALAMAN ORANG TUA MERAWAT ANAK AUTISME USIA 15-17 TAHUN - Susanti, Afriyet; Indiyah, Sri (Universitas Muhammadiyah Magelang, 2018)
Parents’ experience in caring for children with autism is an amazingly hard and uneasybecause parents’ roles are very important in behavioural development of children with autism.Purposes: this research is to get the overview of parents’ experience in caring children withautism in the age of 15–17 at T. C. Clinic. Methods: This research used qualitative method withphenomenology approach. Data sources are collected by in-depth interview and being analysedwith Colaizzi and soft ware N-Vivo. Sampling method in this research is purposive samplingwith 6 interviewees. Results: This research found 8 themes; parents’ knowledge of autism,mom’s feeling, mom’s way to care children with autism, obstacles in caring, readiness to acceptchildren with autism, facing the puberty, autism education and expectation in caring forchildren with autism. Conclusion: Parents believe in different parenting to be implemented tochildren with autism. Parents should understand and adapt the parenting with thedevelopmental needs of children with autism so children will not have prolonged problems intheir behaviour. Pengalaman orangtua dalam merawat anak autis sangatlah berat dan tidak mudah karena peranorang tua sangat penting dalam perkembangan tingkah laku anak dengan autisme. Tujuanpenelitian ini untuk mendapatkan pengalaman orangtua dalam merawat anak autis usia 15-17tahun di T.C. Klinik. Metode: Penelitian ini menggunakan metode kualitatif dengan pendekatanfenomenologi. Sumber data dikumpulkan dengan wawancara mendalam dan dianalisamenggunakan Colaizzi dan software N-Vivo. Metode sampling dalam penelitian ini adalahpurposing sampling dengan 6 narasumber. Hasil: penelitian ini menemukan 8 tema;pengetahuan orangtua tentang autisme, perasaan ibu, cara ibu merawat anak autis, halangandalam merawat, kesiapan untuk menerima anak autis, menghadapi pubertas, pendidikan autismedan ekspetasi dalam merawat anak autis. Kesimpulan: Orangtua percaya dengan pengasuhanyang berbeda-beda untuk diterapkan kepada anak autis. Orangtua harus memahami danmengadaptasi cara pengasuhan dengan perkembangan kebutuhan anak autis sehingga anak-anaktidak akan memiliki masalah dalam tingkah lakunya.